2018
DOI: 10.1111/1750-3841.14219
|View full text |Cite
|
Sign up to set email alerts
|

Muscle‐Specific Mitochondrial Functionality and Its Influence on Fresh Beef Color Stability

Abstract: During retail display tenderloin steaks packaged in PVC overwrap discolor quicker than strip loin steaks. This research determines the basis for muscle-specific differences in color stability. The results indicate that mitochondria present in tenderloin lose its functionality faster than strip loin mitochondria. Developing strategies to minimize muscle-specific differences in mitochondrial changes can increase color stability and value of fresh beef.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In support, DC beef exhibited greater mitochondrial activity and OC than Np beef, as reported previously [12]. In general, PM exhibited greater mitochondrial content and OC than LL of Np beef, as reported by Mancini et al (2018) [30]. The increased mitochondrial activity and content are responsible for the increased OC.…”
Section: Oxygen Consumptionsupporting
confidence: 81%
“…In support, DC beef exhibited greater mitochondrial activity and OC than Np beef, as reported previously [12]. In general, PM exhibited greater mitochondrial content and OC than LL of Np beef, as reported by Mancini et al (2018) [30]. The increased mitochondrial activity and content are responsible for the increased OC.…”
Section: Oxygen Consumptionsupporting
confidence: 81%
“…Color is the parameter that most influences consumer choice, and if it is acceptable, the consumer is likely to ignore all other quality attributes. Consumers perceive color as an indicator of freshness and wholesomeness (Mancini et al, 2018).…”
Section: Color Parameters Of Meatmentioning
confidence: 99%
“…The changes in the color of meat from HF BW bulls, observed in the present study, were a natural consequence of such transformations. During refrigerated storage, changes in meat color result largely from chemical transformations of myoglobin (Mancini et al, 2018). Under increased oxygen partial pressure, myoglobin is converted into the bright red oxymyoglobin.…”
Section: Color Parameters Of Meatmentioning
confidence: 99%
See 1 more Smart Citation
“…Agric. v.79, n.1, e20200079, 2022 has been recently reported (Ramanathan et al, 2019;Mancini et al, 2018). These results indicated that muscle-specific differences in mitochondrial activity may partially contribute to variations in the color stability of longissimus lumborum and psoas major beef muscles.…”
Section: Novelties In Meat Color Studies Of Dark-cutting Beefmentioning
confidence: 53%